Pengembangan Usaha Kecil dan Menengah - Heru Pramana (Jurnal Aplikasi Bisnis, 2017)
This paper analyzes factors that influence the development of micro, Small and Medium Enterprises (MSME) in Indonesia. The variables used in this paper are gross domestic product, bank lending, and labor force. The tools to analyze the problem are the error correction model of Engle and Granger (1987), and the data used for estimation are time-series annual data from 1989-2009. The data analysis shows that all variables in the model significantly influence the number of such enterprises, both in the short run and in the long run.